1994
DOI: 10.1017/s0950268800051682
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofmecA, femA, andfemBgenes in clinical strains of staphylococci using polymerase chain reaction

Abstract: SUMMARYMecA, a structural gene located on the chromosome of Staphylococcus aureus, characterizes methicillin-resistant S. aureus (MRSA), and femA and femB(fem) genes encode proteins which influence the level of methicillin resistance of S. aureus. In order to examine effectiveness of detecting mecA and fem genes in identification of MRSA, the presence of these genes in 237 clinically isolated strains of staphylococci was investigated by polymerase chain reaction (PCR). An amplified mecA DNA fragment of 533 bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 18 publications
5
101
1
7
Order By: Relevance
“…Positive correlation of phenotype with genotype tests were reported for MRSA isolates, which harboured mecA and femB genes [27]. Kobayashi et al reported that mecA was detected in 100 % of MRSA, 16.7 % of MSSA isolates [28]. In Egypt, only few studies have reported the use of femA along with mecA as molecular targets for identification of S. aureus and characterisation of MRSA [12,22] and there were no reports which specifically investigated the prognostic value of femB gene for the detection of S. aureus.…”
Section: Discussionmentioning
confidence: 97%
“…Positive correlation of phenotype with genotype tests were reported for MRSA isolates, which harboured mecA and femB genes [27]. Kobayashi et al reported that mecA was detected in 100 % of MRSA, 16.7 % of MSSA isolates [28]. In Egypt, only few studies have reported the use of femA along with mecA as molecular targets for identification of S. aureus and characterisation of MRSA [12,22] and there were no reports which specifically investigated the prognostic value of femB gene for the detection of S. aureus.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al found a similar finding in a study on MRSA isolates and reported increased expression of this gene in MRSA strains compared to methicillin-susceptible S. aureus (MSSA) strains (9). Kobayash et al detected femA and femB gene in 237 S. aureus isolates and claimed that these two genes could be used for identification of MRSA strains (23). These In this study, microbiological and biochemical methods showed that 43 (39.09%) of 110 milk samples collected were contaminated with S. aureus.…”
Section: Discussionmentioning
confidence: 61%
“…A number of previous studies have assessed the use of PCR-based strategies, with a range of DNA targets, for identification of MRSA [5,10,12,14,151. Most of these studies have been concerned with the specific identification of bacterial strains already isolated in pure culture, although Vannuffel et al [14] were able to detect small numbers of MRSA successfully in freshly collected spiked blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mecA gene is the primary structural requirement for methicillin resistance in staphylococci [8] and has been used as a PCR target in other studies [5,10,12,14,151. It is important to note that DNAbased methods differ from phenotypic techniques in that they examine the genetic potential of an organism to exhibit resistance [20].…”
Section: Discussionmentioning
confidence: 99%